The Strategy of the General Election Supervisory Agency (Bawaslu) in Effort Revive a Democratic Party with Integrity - Beni Ardi (Berpusi Publishing, 2023)
The main objectives of the election monitoring body's strategy are to ensure that elections or other elections take place in a fair, free and transparent manner, ensure that all candidates have equal opportunities to compete in elections, prevent fraudulent practices such as multiple voting, fake voting, or voter intimidation, ensuring that voting and vote counting are carried out correctly and transparently. The method used in writing this article uses the library research method, the purpose of the Library Research research method is to obtain relevant and up-to-date information on the research topic being carried out. Library Research's research method is often used in social research, such as comparative studies, historical research, and qualitative research. The results of this study indicate that the strategy of the election supervisory body has a very strategic role in upholding the integrity of the democratic party. This is done so that supervision of general elections can be carried out in a more transparent and accountable manner.